Efeitos high-stakes em sistemas de accountability low-stakes na educação de municípios catarinenses: High-stakes effects in low-stakes accountability systems in the education of Santa Catarina municipalities (Revista Cocar, 2025)
O estudo investiga a influência de elementos típicos da accountability high-stakes em sistemas formalmente caracterizados como low-stakes, analisando como mecanismos de regulação e controle podem operar mesmo na ausência de sanções explícitas. O objetivo é compreender como esses sistemas exercem influência sobre a gestão educacional e as práticas pedagógicas, sem necessariamente implantar modelos high-stakes. A pesquisa tem uma abordagem documental e incide em seis municípios catarinenses, considerando a forma como a regulação por resultados se manifesta nesses contextos. Os resultados indicam que, ainda que não prevejam punições diretas, sistemas low- stakes podem gerar impactos semelhantes aos high-stakes, impulsionando mudanças na gestão educacional e práticas pedagógicas por meio da ênfase em metas e indicadores educacionais.Palavras-chave: Sistemas high-stakes e low-stakes; Accountability educacional; Regulação por resultados.AbstractThe study investigated the influence of elements typical of high-stakes accountability in systems characterized as low-stakes, analyzing how regulation and control mechanisms can operate even without explicit sanctions. The aim is to understand how these systems influence educational management and pedagogical practices, not necessarily implementing high-stakes models. The research has a documental approach and encompasses six Santa Catarina municipalities, considering how result-based regulation appears in these contexts. The results indicate that, though no direct punishment was foreseen, low-stakes systems can create similar impacts as high-stakes ones, promoting changes in educational management and pedagogical practices by emphasizing educational targets and indicators.Keywords: High-stakes and low-stakes systems; Educational accountability; Result-based regulation.
Keywords: Sistemas high-stakes e low-stakes; Accountability educacional; Regulação por resultados.